Estimating of Coffee Plantation Carbon Stock in Jatikerto and Surrounding Areas - Bagas Andreansyah; Nisfi Fariatul Ifadah; Soemarno (Nusantara Science and Technology Proceedings, 2022)
The increase in human population causes several negative impacts, one of which is the extreme climatic changes. The main cause of this climatic changes is global warming due to the increase in greenhouse gases (GHG) such as CH4, CO2, and NO2 in the atmosphere where this is caused by the burning of fuel for motor vehicles and factories, as well as a decrease in carbon-absorbing plant vegetation due to the clearing of new land. This research is to estimate how much coffe plantation in ATP Jatikerto contribute on containing carbon stock. The methods used in this study namely non destructive by adhering to SNI-7724 which recommends estimating carbon stocks using an allometric model, the types of plants at the observation site were Coffea liberica, Coffea canephora, Gliricidia sp., Leuceana sp., Musa sp., and Theobroma cacao. There are 4 vegetation structures at the observation site, namely C. liberica with Gliricidia sp., then C. canephora with Gliricidia sp., then C. canephora with Leuceana sp., and C. canephora with Musa sp.